Peran Pengelola Wisata Pulau Tubir Seram Dalam Mewujudkan Kesejahteraan Sosial-Ekonomi Masyarakat Dana Weria - Ahmad Khumaidi; Agus Riyadi; Abdul Karim; Asep Firmansyah (Pascasarjana IAIN Metro, 2026)
Tubir Seram Island in Fakfak Regency, West Papua, has tourism potential that can support the socio-economic welfare of the Dana Weria community. However, tourism development is constrained by limited infrastructure, low digital literacy, and geographical challenges. This study aims to analyze the management of Tubir Seram Island tourism and its contribution to community welfare. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving tourism managers, visitors, and members of the Dana Weria community. The findings show that community-based tourism management contributes to increasing household income, creating employment opportunities, and strengthening local cultural identity. Nevertheless, inadequate infrastructure, limited human resource capacity, and weak stakeholder coordination remain major challenges to sustainable tourism development. This study contributes to the community-based tourism literature by providing empirical evidence from a remote coastal area in West Papua. The findings emphasize the importance of strengthening local institutions, enhancing tourism capacity-building programs, and increasing government support to promote inclusive and sustainable tourism development. Effective tourism management can serve as a strategic instrument for improving the socio-economic welfare of coastal communities.